Trypanosomiasis in N'Dama cattle under village management in Zaire - Ngamuna, S.; D'Ieteren, G.D.M.; Itty, P.; Leak, S.G.A.; Maehl, J.H.H.; Minengu, M.; Nagda, S.M.; Paling, R.W.; Rarieya, J.M.; Thorpe, W.R.; Trail, J.C.M. (1988)
The prevalence, species and intensity of trypanosome parasitaemia over an eighteen-month period, February 1986 to July 1987, are reported for some 700 N`Dama cattle managed in twenty-five village herds in forest and plateau areas of Idiofa, Zaire. The effect of trypanosomiasis and other diseases on PCV was reported. Mean monthly PCV for the total population was 34.9%, with some variation between areas (forest 34.2%, plateau 35.6%) and large variation between herds (31.6 to 40.7). Mean past-partum weight of N`Dama cows in this population was 232 kg, and mean calf weights at 8 and 12 months were 88 and 105kh, respectively. These preliminary results on the health and performance of N`Dama cattle managed in village herds at trypanosomiasis risk were a good illustration of the trypanotolerance of the N`Dama.